Disturbio digestivo en el bovino caracterizado por hipermotilidad del rumen - Alba, Jorge de; Morillo, Francisco J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A disorder observed in dairy cattle in the bumid tropics of Costa Rica is described The fundamental characteristic of this disorder is the great irregularity of the rumen contractions. The interval between contractions tend to become shorter and, in advanced cases, the undulating movements are continuous in the ventral section of the rumen The malady bas no apparent cause and clears up in from a few days to a month and a half However, as it is accompanied by a drastic reduction in milk production that often terminates the lactation emly, it is of economic importance